Prognostic Role of Right Ventricular Function in Patients With Heart Failure Undergoing Cardiac Resynchronization Therapy. Issue 11 (28th July 2016) - Rapacciuolo, Antonio; Maffè, Stefano; Palmisano, Pietro; Ferraro, Anna; Cecchetto, Antonella; D'Onofrio, Antonio; Solimene, Francesco; Musatti, Paola; Paffoni, Paola; Esposito, Francesca; Parravicini, Umberto; Agresta, Alessia; et al.
Abstract : Background: Because 20% to 40% of patients undergoing cardiac resynchronization therapy (CRT) do not respond to it, identification of potential factors predicting response is a relevant research topic. Hypothesis: There is a possible association between right ventricular function and response to CRT. Methods: We analyzed 227 patients from the Cardiac Resynchronization Therapy Modular Registry (CRT‐MORE) who received CRT according to current guidelines from March to December 2013. Response to therapy was defined as a decrease of ≥15% in left ventricular end‐systolic volume (LVESV) at 6 months. Results: The tricuspid annular plane systolic excursion (TAPSE) value that best predicted improvement in LVESV (sensitivity 68%, specificity 54%) was 17 mm. Stratifying patients according to TAPSE, LVESV decreased ≥15% in 78% of patients with TAPSE >17 mm (vs 59% in patients with TAPSE ≤17 mm; P = 0.006). At multivariate analysis, TAPSE >17 mm was independently associated with LVESV improvement (odds ratio: 1.97, 95% confidence interval: 1.03‐3.80, P < 0.05), together with ischemic etiology (odds ratio: 0.39, 95% confidence interval: 0.20‐0.75, P < 0.01). These results were confirmed for New York Heart Association class III to IV patients (79% echocardiographic response rate in patients with TAPSE >17 mm vs 55% in patients with TAPSE <17 mm; P = 0.012). Conclusions: Baseline signs of right ventricular dysfunction suggest possible remodeling after CRT. A TAPSE value of 17 mm was identified as a good cutoff for predicting a better response to CRT in patients with both mildly symptomatic and severe heart failure.